2018
DOI: 10.1128/jvi.00588-18
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Recombinant Rotaviruses Expressing Fluorescent Proteins by Using an Optimized Reverse Genetics System

Abstract: An entirely plasmid-based reverse genetics system for rotaviruses was established very recently. We improved the reverse genetics system to generate recombinant rotavirus by transfecting only 11 cDNA plasmids for its 11 gene segments under the condition of increasing the ratio of the cDNA plasmids for NSP2 and NSP5 genes. Utilizing this highly efficient system, we then engineered infectious recombinant rotaviruses expressing bioluminescent (NanoLuc luciferase) and fluorescent (enhanced green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
140
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 39 publications
5
140
0
Order By: Relevance
“…To determine whether this hypothesis is correct or not, it is necessary to evaluate the superiority of G1 type VP7 and P [8] type VP4 in RVA infection by using a reverse genetics system of RVA in future studies. [19][20][21] Gene rearrangements have been detected in chronic RVA infection in immunodeficient children, 22,23 and in vitro during passages at a high multiplicity of infection in cell culture. 24,25 Since PAGE analysis suggested that the gene rearrangements occurred in several genes including NSP5 gene in RVAs collected from the patient (Figure 2), sequence analysis was carried out to confirm the gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether this hypothesis is correct or not, it is necessary to evaluate the superiority of G1 type VP7 and P [8] type VP4 in RVA infection by using a reverse genetics system of RVA in future studies. [19][20][21] Gene rearrangements have been detected in chronic RVA infection in immunodeficient children, 22,23 and in vitro during passages at a high multiplicity of infection in cell culture. 24,25 Since PAGE analysis suggested that the gene rearrangements occurred in several genes including NSP5 gene in RVAs collected from the patient (Figure 2), sequence analysis was carried out to confirm the gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…All antibodies were used at manufacturer's recommended dilution. Rabbit polyclonal antibodies against RV‐SA11 structural proteins VP1 and VP4 (Komoto et al, ) and nonstructural proteins NSP1 (Komoto et al, ), NSP3, NSP4, and NSP5 (Komoto et al, ) were raised according to standard protocols at the Department of Virology and Parasitology, Fujita Health University School of Medicine, Aichi, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, a versatile entirely plasmidbased reverse genetics system was developed recently (14). Entirely plasmid-based reverse genetics systems have been developed only for a single animal RVA strain, simian SA11-L2, which grows to high titers in cell cultures (14)(15)(16). Three strategies for entirely plasmid-based reverse genetics have been developed for this animal virus.…”
mentioning
confidence: 99%